Pendampingan Pelaporan SPT PPH Orang Pribadi dan Sosialisasi PMK Nomor 168 Tahun 2023 - Riza Edwindra; Desak Rurik Pradnya Paramitha Nida; I Made Sastra Dwikiarta (Universitas Warmadewa, 2024)
before the end of March. Tax return reporting is mandated in the Law on General Provisions and Tax Procedures (KUP) article 3, where every taxpayer is required to fill out the tax return correctly, clearly and completely, and for the annual income tax return, it must be submitted no later than 3 months after the tax year ends (March). Tax return reporting can be done online, using e-form or e-filling. However, there are still many people who still do not understand the reporting process using e-filling. The people in the Renon area are very homogeneous. The Renon area is considered very promising, until now it is still an